Altered EPS Protein Secretion in Salmonella Typhimurium Biofilm Following Treatment with DMSO - F Z Raja Yahya, M; Alias, Z; A Karsani, S (International Journal of Engineering and Technology, 2019)
Dimethyl sulfoxide (DMSO) is known to inhibit biofilm formation by Salmonella typhimurium and cause infrared spectral variations of extracellular polymeric substance (EPS) matrix. However, the impact of DMSO treatment on EPS protein secretion in S. typhimurium biofilm remains not well investigated. The present study was performed to investigate the EPS protein profile of S. typhimurium biofilm following treatment with DMSO. Biofilm was developed in 6-well microplate at 37 OC for 24 hours. Quantitative resazurin assay and infrared spectroscopy were performed to determine biofilm viability and cell surface chemistry respectively. Subtractive EPS protein profiling was carried out using a combination of polyacrylamide gel electrophoresis and tandem mass spectrometry. Treatment with 32% DMSO caused significant reduction in biofilm viability and alteration of cell surface chemistry. Subtractive comparison of EPS protein profiles highlighted one unique protein band, 52.1 kDa, which was secreted only in 32% DMSO treated EPS matrix and not in control EPS matrix. In turn, three EPS proteins were successfully identified from the 51.2 kDa protein band. In conclusion, altered EPS protein secretion following treatment with 32% DMSO may mediate inhibition of S. typhimurium biofilm.Â Â